PENGARUH STRATEGI BELAJAR AKTIF TIPE PEER LESSON TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 PADANG SAGO KABUPATEN PARIAMAN - Pardinal, Opi Yoke; Aima, Zulfitri; Cesaria, Anna (STKIP PGRI Sumbar, 2013)
This research is motivated by the students comprehension of mathematics concepts are still low. Learning process tends to take place in one direction. Less resource book. Students do not what to think of doing exercises and would rather wait for an answer from a friend who has more capacity. Based on observations in class VIII SMPN1 Padang Sago Pariaman found in the working practice so that studentsare not accustomedto discuss individual students are more likely to be individual in the study. This study aims to determine whether students comprehension of mathematics concepts by applying active learning strategies Peer Lesson type better than student comprehension of mathematics concepts by applying conventional learning in class VIII SMPN1 Padang Sago Pariaman 2012/2013. This type of researchis is experimental research design randomized trials on the subject. The population in this study were all students of class VIII to class VIII.3 sample as the experimental class and the control class as a class VIII.1. Instrument in this study is a test of comprehension of mathematics concepts in the form of essays with a reliability test is r_11 = 0.784. The data analysis technique used is the t-test with Minitab . Based on the test results obtained by the hypothesis P - value = 0.007 is smaller than the specified significance level of 0.05 . Thus, students comprehension of mathematics concepts by applying active learning strategies Peer Lesson type better than conventional learning in class VIII SMPN1 Padang Sago Pariaman at the level of 95 %